2014
DOI: 10.3390/ph7040464
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Monitoring of the Antiangiogenic Effect of Neurotensin Receptor-Mediated Radiotherapy by Small-Animal Positron Emission Tomography: A Pilot Study

Abstract: The neurotensin receptor (NTS1) has emerged as an interesting target for molecular imaging and radiotherapy of NTS-positive tumors due to the overexpression in a range of tumors. The aim of this study was to develop a 177Lu-labeled NTS1 radioligand, its application for radiotherapy in a preclinical model and the imaging of therapy success by small-animal positron emission tomography (µPET) using [68Ga]DOTA-RGD as a specific tracer for imaging angiogenesis. The 177Lu-labeled peptide was subjected to studies on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 42 publications
(50 reference statements)
2
29
0
Order By: Relevance
“…The first preclinical study on a 177 Lu- Table 3). 49 Applying a single high-activity treatment of 50 MBq [ 177 Lu]Lu-NT127 per animal caused a significantly decreased tumor diameter of approximately 50% in HT29-tumor-bearing nude mice in vivo, an effect that was superior compared with that obtained from the administration of 2 or 4 fractionated doses. 47 This study showed that a relatively high dose of a 177 Lu-labeled peptide was necessary for inhibiting the HT29 tumor growth in vivo, and, moreover, that severe fibrotic lesions were detected in kidney and liver sections, which might hamper the translation of the NTS1-mediated radiotherapy approach with [ 177 Lu]Lu-NT127 into human applications in the future.…”
Section: Peptides Radiolabeled With Lu-177 For Endoradiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The first preclinical study on a 177 Lu- Table 3). 49 Applying a single high-activity treatment of 50 MBq [ 177 Lu]Lu-NT127 per animal caused a significantly decreased tumor diameter of approximately 50% in HT29-tumor-bearing nude mice in vivo, an effect that was superior compared with that obtained from the administration of 2 or 4 fractionated doses. 47 This study showed that a relatively high dose of a 177 Lu-labeled peptide was necessary for inhibiting the HT29 tumor growth in vivo, and, moreover, that severe fibrotic lesions were detected in kidney and liver sections, which might hamper the translation of the NTS1-mediated radiotherapy approach with [ 177 Lu]Lu-NT127 into human applications in the future.…”
Section: Peptides Radiolabeled With Lu-177 For Endoradiotherapymentioning
confidence: 99%
“…To date, only a few studies have reported on the preclinical radiotherapeutic efficacy of 177 Lu‐labeled NT peptide analogs. The first preclinical study on a 177 Lu‐labeled peptide was reported by Maschauer et al, who used [ 177 Lu]Lu‐NT127 (K i = 30 nM), a Lys‐elongated NT(8–13) analog with the DOTA chelator attached via a PEG 6 ‐spacer at the N ɛ ‐position (entry 6, Table ) . Applying a single high‐activity treatment of 50 MBq [ 177 Lu]Lu‐NT127 per animal caused a significantly decreased tumor diameter of approximately 50% in HT29‐tumor‐bearing nude mice in vivo, an effect that was superior compared with that obtained from the administration of 2 or 4 fractionated doses .…”
Section: Introductionmentioning
confidence: 99%
“…Internalization and efflux experiments were conducted using HT29 cells in 24-multiwell plates and 0.5 MBq of each radiotracer as described before. 21 The experiments were performed in quadruplicate and were repeated at least twice. kidneys, heart, spleen, brain, muscle, femur and intestine) and blood were removed and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…by the introduction of non-natural amino acids or by variations of the amino bonds. [12][13][14][15][16][17][18][19][20][21][22][23] In principle, PET allows non-invasive in vivo imaging of receptors expressed on tumors with excellent sensitivity and precise quantification of receptor densities and therefore PET is a highly powerful imaging modality in nuclear medicine, provided that suitable radioligands for in vivo use are available. 24 Most of the previously developed radiolabeled NT derivatives were labeled with nuclides suitable for single photon emission tomography (SPECT) or radiotherapy, [25][26][27] however, only a limited number of NT derivatives were radiolabeled with an isotope suitable for PET imaging studies, such as fluorine-18 or gallium-68.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas recently some efforts were made to develop peptide analogs with specific binding to neurotensin receptors [131] [132] as well as hybride peptide tracers [133] [134], there are only few non-peptide lead structures for high affinity and specific neurotensin receptor ligands available.…”
Section: Neurotensin Receptor Ligandsmentioning
confidence: 99%